The trend of dystopia in contemporary Croatian prose - Gajin, Igor (Anafora, 2022)
In contemporary Croatian prose from 2010 to the present day, there has been an abundant series of novels with dystopian content that has introduced, so to speak, a new genre in the Croatian literary tradition, since in the diachrony of this national literature the dystopian themes have barely been represented. The paper intends to construe the cultural context of the cause of this phenomenon and point to the link in the structure of feelings formed by the processes of transition, globalization and neoliberal capitalism with the manifestation of the intensification of the dystopian genre as a motivated discursive manoeuvre by which social criticism is moved from the present “realistic prose” to “fantasy” imaginings of the future.